The rise in incidence of pediatric type 2 diabetes during the COVID-19 pandemic and the virus as a potential causative factor - Andrew Kanouse; Joanna S. Fishbein; Parissa Salemi (Diabetes Epidemiology and Management)
Aim: The prevalence of type 2 diabetes continues to rise across multiple demographics but there was an especially large increase in incidence during the COVID-19 pandemic. A pre-existing diagnosis of type 2 diabetes is generally associated with more difficulties with viral infections, as seen with COVID-19, but it is less clear if a reverse causal association exists between the development of type 2 diabetes and infection with the COVID-19 virus. Our aim was to determine if an association exists between the COVID-19 virus and new diagnoses of pediatric type 2 diabetes. Methods: We examined 130 new patients in our pediatric endocrinology practice diagnosed with type 2 diabetes immediately before and just after the emergence of the pandemic to determine if there was a change in presenting characteristics between these two periods. Results: Our data showed an increase in the incidence of type 2 diabetes (p < 0.0001) and a lower mean presenting age (p = 0.03) during the COVID-19 pandemic without differences in other parameters. Conclusion: We believe these results suggest that the development of type 2 diabetes following COVID-19 infection is due to mechanisms inherent to the virus itself and that younger patients are especially at an increased risk.